1999
DOI: 10.2472/jsms.48.3appendix_28
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of Ionomers Based on Ethylene-Co-Methacrylic Acid Copolymer (Emaa)

Abstract: Fourier-transform infrared spectra (FTIR) measurement was made on zinc and sodium ionomers (EMAA-Zn and EMAA-Na) of ethylene-co-methacrylic acid copolymer. It was found that the asymmetry stretching vibration peak of CO bond of COO-group in ion aggregates of EMAA-Na appeared at lower wavenumber, compared with EMAA-Zn. This means that complete and stable ion aggregates exist in EMAA-Na. Differential scanning calorimetry (DSC) measurement showed that endotherm peak (T1) in lower temperature range resulted from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…3) 一方,Znタイプのアイオ ノマーでは,普通4配位4面体型の配位構造を形成する.これ はZn金属1個あたり4個の酸素原子が配位できることを意味 するが,Zn金属は2価のイオンであることから,イオン結合 するカルボキシレート(-COO-)だけで,それ以外のものは 配位できない. 10-11), [22][23][24] 以上のことから,本研究の結果を考えると,イオン凝集体 内に未中和カルボン酸が配位し,入り込める可能性があるの は,EMAA-54Na にStMAAをブレンドした時のみである.こ のことから判断すると,未中和のカルボン酸を含むStMAAは …”
unclassified
“…3) 一方,Znタイプのアイオ ノマーでは,普通4配位4面体型の配位構造を形成する.これ はZn金属1個あたり4個の酸素原子が配位できることを意味 するが,Zn金属は2価のイオンであることから,イオン結合 するカルボキシレート(-COO-)だけで,それ以外のものは 配位できない. 10-11), [22][23][24] 以上のことから,本研究の結果を考えると,イオン凝集体 内に未中和カルボン酸が配位し,入り込める可能性があるの は,EMAA-54Na にStMAAをブレンドした時のみである.こ のことから判断すると,未中和のカルボン酸を含むStMAAは …”
unclassified
“…These ionomer related peaks (Figure 5 and the peak at 1584 cm −1 is related to the asymmetric stretching vibration of the C−O bond in tetra-coordinated zinc carboxylates. [90][91][92] FTIR measurements confirmed that there is an interaction between the ionomer and the other components of the blend. In particular a slight shift to higher wavenumber for C-O vibrations of POM (indicated by the symbols * and @ in Figure 6(d)) and of Zn 2+ ionomer due to the interaction between the pedant ions of EMAA-Zn 2+ and the dipoles of POM was detected.…”
Section: Resultsmentioning
confidence: 75%
“…It can be seen that there are peaks present due to the presence of the ionomer. These ionomer related peaks (Figure 5(d)), such as those at 1734 and 1697 cm −1 are ascribed to ester carbonyl group and carboxylic acid group, and the peak at 1584 cm −1 is related to the asymmetric stretching vibration of the C−O bond in tetra‐coordinated zinc carboxylates 90–92 . FTIR measurements confirmed that there is an interaction between the ionomer and the other components of the blend.…”
Section: Resultsmentioning
confidence: 83%